Yusufnomics, model APBN Qurani kebal krisis: strategi Yusuf as menangani krisis pangan berkepanjangan di Mesir - Harun, Chairullah (UPT Publikasi Ilmiah, 2024)
The government budget is a projection of government revenues and expenditures for a certain period. Government revenues consist mostly of taxes, while expenditures consist of government spending. In Indonesia, the State Revenue and Expenditure Budget, abbreviated as APBN, must be approved by the House of Representatives. The APBN is designed to ensure that the country's economy can continue to move even amidst various challenges, in order to create a prosperous, just and prosperous society. The APBN is called a Surplus if government Revenue is greater than Expenditure. The surplus becomes State Savings. The APBN is called Balanced, if government revenues are the same as expenditure. The APBN is called a deficit if government revenue is smaller than expenditure. The deficit must be covered with debt. Yusufnomic, is a simple Surplus APBN model, which has proven successful in saving Egypt from a prolonged food crisis, based on noble and strong values, namely optimizing production, the state and society saving money when prosperous, the vision and example of leaders and the determination to overcome the crisis with reserves or savings of the state and society . Yusufnomics also suggests that success really depends on the character of the leader. And as God's chosen man, Yusuf (a.s.) has steadfast faith, is visionary, firm and professional.